2020
DOI: 10.1177/2325967120s00464
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Arthrofibrosis in Tibial Spine Fractures: A National 10-Site Multicenter Study

Abstract: Objectives: To identify risk factors for developing arthrofibrosis after TSF treatment. Methods: This was a retrospective, multi-center study across ten institutions of 448 patients <25 years old who presented to care with a tibial spine fracture between 1/2000 and 2/2019. Patient records were reviewed for a multitude of pre-operative, intra-operative, and post-operative characteristics. Patients were then separated into two cohorts based on if they suffered from post-treatment arthrofibrosis. Results: Char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This remains the most common postoperative complication after fixation of TSFs, with a reported incidence ranging from 10% to 29% and frequently requiring reoperation. 4,13,27,33 Watts et al 33 previously found that operative time ≥120 minutes and delay of surgery >7 days from injury led to increased rates of arthrofibrosis. These findings, as well as ours, suggest that there may be an additive effect of delayed surgery, prolonged surgery time, and injury severity on the risk of postoperative stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…This remains the most common postoperative complication after fixation of TSFs, with a reported incidence ranging from 10% to 29% and frequently requiring reoperation. 4,13,27,33 Watts et al 33 previously found that operative time ≥120 minutes and delay of surgery >7 days from injury led to increased rates of arthrofibrosis. These findings, as well as ours, suggest that there may be an additive effect of delayed surgery, prolonged surgery time, and injury severity on the risk of postoperative stiffness.…”
Section: Discussionmentioning
confidence: 99%